Metadata standards for resource description of the Library of Congress (Libellarium: journal for research in the field of information and related sciences, 2023)
Objective. The aim of the paper is to present the development of metadata standards for resource description – or metadata schemas – of the Library of Congress in Washington, USA, initiated by the accelerated development of technology and the growth of the networkenvironment in recent decades.Approach/Methodology/Design. In line with the paper’s objective, the selected approach is reduced to a summary of the development of each metadata standard of the Library of Congress individually, with a focus on metadata schemas for resource description within the library community – MARC 21, MARCXML, MODS and MADS. This approach enables the authors to analyze and evaluate in detail the current state of metadata standards and their evolution over time, as well as to identify challenges and opportunities for future development.Results. The paper provides a concise overview of the development of each metadata standard at the Library of Congress individually with a focus on the metadata schemes for resource description within the library community – MARC 21, MARCXML, MODS, and MADS. It also provides an overview of the development of metadata schemes for resource description in related communities (EAD, VRA Core) and metadata standards for digital librariesintended for archiving and protection (METS, PREMIS). The paper also discusses potential directions for further development of metadata standards in the Library of Congress, with reference to projects related to semantic web and related data technologies (BIBFRAME, MODS/RDF, MADS/RDF). The need for continuous improvement of metadata standards is emphasized in order to provide better services to users and harmonize them with technological development and user needs.Originality/Value. The paper provides a comprehensive overview of the development of the Library of Congress metadata standards, which is of great importance to the library community and those engaged in archiving and preservation of digital resources. A discussion of possible directions for the development of metadata standards, particularly in the context of the Semantic Web and Linked Data, provides insight into future challenges andopportunities for the Library of Congress and the wider community. Ultimately, this paper contributes to the understanding of the importance and complexity of metadata standards and their continuous development in the light of rapid technological changes.
Keywords: Library of Congress; MARC 21; metadata; metadata schemas; metadata standards